SISTEM INVENTARISASI PENGGUNAAN PERALATAN DAN BAHAN PADA MEJA PRAKTIKUM PLC DI POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG MENGGUNAKAN BARCODE SCANNER - Nofriyani Nofriyani; Adhi Budiono; Charlotha Charlotha; Indra Dwisaputra; Dedy Ramdhani (Gema Teknologi, 2021)
In the Programmable Logic Controller (PLC) course at Polmanbabel, students use a practicum table containing practicum equipment such as computer units, compressors, PLC units, pneumatic valves, sensors, jumper cables, etc. Before and after practicum, students are required to do an inventory of equipment and materials contained on this practicum desk. The inventory process is still done manually, where students write the name of the equipment, check the presence of the equipment, and calculate the amount. The thing that was complained by lecturers was the confiscation of practicum time as a result of the manual inventory process. Based on this, a new inventory system was created that uses the application and is equipped with a barcode scanner that is able to minimize the time and possibility of misplacement of the device. Based on the results of experiments, it can be seen that this system is able to minimize inventory time by an average of 14.65 minutes compared to manual inventory systems.